How Do We Do It? The English Language Proficiency of Second Language Learners in the Foundation Phase of an English Medium School: Challenges and Strategies - Badenhorst, J.W.; van der Merwe, M.M. (J Soc Sci, 2015)
The language of instruction in South Africa is currently a very controversial issue. As a result of South Africa’s political history, English is almost always chosen as the language of instruction. However, in many cases, as is the case in the current study, the learners have not been adequately exposed to English when they enter the Foundation Phase. This study reports research conducted at a former privileged primary school in South Africa with English as the Language of Learning and Teaching (LoLT). The aim of the study was to explore the practices implemented by the Foundation Phase teachers to teach the learners English, and to ascertain how the school has managed to maintain a consistently high academic standard, despite the language difficulties of their learners. The findings of the study may be of value to schools which are faced with similar challenges as the sample school.
Pulished Article
Keywords: Second Language Acquisition; Language of Learning; Teaching